PENGARUH PELATIHAN YOGA ASANA (SURYANAMASKAR) TERHADAP KELENTUKAN DAN KAPASITAS VITAL PARU - Mertayasa, Ketut (Universitas Pendidikan Ganesha, 2013)
This research aimed to determine the effect of yoga asana (suryanamaskar) training on flexibility and lung vital capacity. A quasi-experiment research using the non-randomized control group pretest-posttest design was used in this research. Subject in this research were 30 male participants of extracurricular yoga at SMA N 2 Banjar in academic year 2012/2013. The flexibility measured by sit and reach instrument with reliability of the test was 0.92 ,while lung vital capacity measured by spirometer instrument with reliability 0.99. The data was analyzed by independent t-test with SPSS 16. The result of independent t-test for flexibility obtained tc of 3.390 with significance 0.002, while the lung vital capacity obtained tc of 2.197 with significance 0.036. The significance of tc was less than α (0.05), meant that the hypotheses which stated that yoga asana (suryanamaskar) training was affecting the flexibility and lung vital capacity could be accepted. From the results of this research could be concluded that yoga asana (suryanamaskar) training was affecting the improvement of flexibility and lung vital capacity.